Psikoedukasi Strategi Koping yang Ideal bagi Orangtua ABK di YPAC Semarang: Psychoeducation on Ideal Coping Strategies for Parents of Children with Disabilities at YPAC Semarang - Trisnadewi, Benedicta Audrey Putri; Kumalasari, Ervina; Rahayu, Puspita Puji (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Parents of special needs children face different challenges compared to other parents. This makes parents of special needs children more vulnerable to stress when caring for their children. Parents of special needs children can reduce their stress levels if they apply effective stress coping strategies that are ideal for them, but it has been found that parents of special needs children tend to apply maladaptive coping strategies. Parents of special needs children at YPAC Semarang are also found to use maladaptive coping strategies and, therefore need to be educated about ideal and effective coping strategies. The psychoeducation program aimed to provide knowledge about ideal coping strategies for parents of special needs children, and was attended by 82 parents of special needs children. This psychoeducation activity succeeded in increasing the knowledge of parents of special needs children about ideal stress coping strategies. Mindfulness-based coping strategy training is recommended for parents of special needs children.